Shellyseer: A Literary Evolution - Fathieh Hussam Saber (15445391) (2023)
The dramatic elements that are in Shellyseer have traveled for a long period of time and have been affected by dramatic elements from different cultures, which means that Shellyseer is a result of the evolution of drama. This chapter draws attention to the effect that the East and the West have on each other, by pointing out the effect that Aristotle’s Poetics—Western Theory—had on Ghanem Al-Suliti’s Shellyseer—Eastern Literature. This chapter combines comparative literature with literary theory and criticism in order to give an example of a globalized view of how drama evolves where there are no borders that limit influence. This chapter traces back drama back to its oldest documented sources to show how it evolved throughout history and offers deeper knowledge of Middle Eastern drama, the importance, and strength of political satire, and how strong of a mutual influence Eastern and Western literature have on each other. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_22